1987
DOI: 10.1111/j.1439-0418.1987.tb00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Megastigmus strobilobius Ratzeburg, 1848 (Hym., Torymidae): its morphology, life history and economic significance

Abstract: Investigations carried out in various French and Polish spruce stands from 1975 to 1986 allowed to precise the stages of development, life history, distribution and economic significance of the spruce seed chalcid, M. strobilobius Ratz. Insect life cycle appears to be quite well adapted to the characteristics of its hosts, Norway and Siberian spruces, and especially to the asynchronic fluctuations in seed crop. Seed damage is generally limited (less than 5 % of the sound seed), but may occasionnally increase u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…For M. strobilobius single‐species attacks occurred only in 4% of the infested cones whereas for the other species this rate varied from 15 to 32%. The low rate for M. strobilobius reflects the fact that it is the latest species to attack spruce cones and in general colonizes only seeds left undamaged by other insects (S krzypczyńska and R oques , 1987).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For M. strobilobius single‐species attacks occurred only in 4% of the infested cones whereas for the other species this rate varied from 15 to 32%. The low rate for M. strobilobius reflects the fact that it is the latest species to attack spruce cones and in general colonizes only seeds left undamaged by other insects (S krzypczyńska and R oques , 1987).…”
Section: Resultsmentioning
confidence: 99%
“…A common trait of the species association of Norway spruce cones reported in the literature was the dominance of the spruce cone moth C. strobilella (SKRZYPCZYN Â SKA, 1982;SKRZYPCZYN Â SKA and ROQUES, 1987). Likewise for Switzerland, WERME- LINGER et al (1995) showed that this species outnumbers all other seed-feeding insects when reared from spruce cones harvested in the ®ve production regions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because M. strobilobius oviposit at the beginning of seed maturity in fully grown cones (Annila 1981, Skrzypczynska andRoques 1987), they are most likely dependent of fertilized seeds (Þlled seeds) for larval development. This is in contrast to M. spermotrophus Wachtl., which oviposit before seed fertilization and can develop in unfertilized seeds of Douglas Þr by preventing seed abortion (e.g., Niwa andOverhulser 1992, Rouault et al 2004).…”
Section: Figmentioning
confidence: 99%
“…Two other pest species that can cause serious damage in some years are Plemeliella abietina Seitner (Diptera: Cecidomyiidae) and Megastigmus strobilobius Ratz. (Hymenoptera: Torymidae) (Annila 1966, Annila 1973, Skrzypczynska and Roques 1987. Three species (S. anthracina, P. abietina, and C. strobilella) oviposit during ßowering, and three species (D. abietella, E. abietaria, and M. strobilobius) oviposit on cones (Annila 1979(Annila , 1981Roques 1983).…”
mentioning
confidence: 98%